Dinâmica da cadeia produtiva do açaí no Amazonas: análise dos preços pagos ao produtor e caracterização do perfil produtivo - Rufino, João Paulo Ferreira (Brasil, 2024)
The objective of this study was to analyze the dynamics of the açaí production chain in the Amazonas region using ARIMA models to understand the dynamics of prices paid to producers and characterize the productive profile through the estimation of production using panel data models. From the delineation of the study area and microregions according to the classification of the Institute of Agricultural and Sustainable Forestry Development of the State of Amazonas (IDAM), data was collected secondarily directly from the database of the aforementioned institution for the period from 2010 to 2022, with cumulative data for January to December periods. The data were divided into two parts: 1) productive data, for the purpose of describing the productivity of the chain in the state and econometric analysis of production; and 2) data on the price paid per kg to the producer for SARIMA analysis and evaluation of the quality of different econometric models employed in forecasting prices received by açaí producers. From the results of this study, it was observed that açaí production in Amazonas is concentrated in the Rio Negro/Solimões microregion, representing between 42% and 58% of the total state production. Other microregions, such as Madeira, Médio Amazonas, and Purus, also contributed significantly. Overall açaí production in the state showed growth from 2010 to 2022, with the transition from an extractivist model to a cultivation-based production, especially in the main producing microregions. However, extractivism still plays a significant role in production. Technological transition also affected the number of producers, with a notable increase in cultivation activity, surpassing, in some cases, participation in extractivism in 2021 and 2022. The analysis of productive yields shows a gradual evolution, with emphasis on the year 2022. The econometric model reveals that the average price to the producer and the number of producers are the most influential variables in açaí production in Amazonas. Although productive yield has a positive impact, its relevance is limited due to the strong representation of extractivism. The SARIMA model highlights the dependence on prices in previous periods, stationarity in the time series of prices, and the presence of seasonality, indicating the influence of seasonal variations. The forecast suggests a trend of price increase for the year 2023.